2022
DOI: 10.1177/10870547221129311
|View full text |Cite
|
Sign up to set email alerts
|

Does Assessment Format Matter? A Comparison of In-Person Versus Teletesting Scores for Youth with ADHD

Abstract: Objective: This study examined test score equivalency between traditional in-person assessment and teletesting among youth diagnosed with Attention-Deficit/Hyperactivity Disorder (ADHD). Method: In all, 896 youth with ADHD, ages 5–21 years, were administered cognitive, academic achievement, and verbal fluency measures via either teletesting ( n = 448) or traditional in-person assessment ( n = 448). The teletesting and in-person groups were matched on age, sex, and insurance type (as a proxy for income). Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 16 publications
0
7
0
1
Order By: Relevance
“…Furthermore, a 100% completion rate for the WEMWBS‐ID was achieved, with no missing data. It may be important in future to also check that scores on the adapted WEMWBS completed via video link (as in the current study) and face‐to‐face are equivalent, although we note that existing evidence does suggest that there can be a high degree of equivalence between face‐to‐face and online/telehealth assessment (McDermott et al ., 2023) including in the context of ID (Hodge et al ., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a 100% completion rate for the WEMWBS‐ID was achieved, with no missing data. It may be important in future to also check that scores on the adapted WEMWBS completed via video link (as in the current study) and face‐to‐face are equivalent, although we note that existing evidence does suggest that there can be a high degree of equivalence between face‐to‐face and online/telehealth assessment (McDermott et al ., 2023) including in the context of ID (Hodge et al ., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…T A B L E 2 Multinomial logistic regression model for association between timeframe (pandemic vs. pre-pandemic) and diagnostic certainty. given emerging literature about telehealth administration equivalency to in person administrations (Hamner et al, 2021;Harder et al, 2020;McDermott et al, 2023;Ng et al, 2023;Wright, 2020). Similarly, some physicians informally adapted developmental assessments previously done in person including the Clinical Linguistic and Auditory Milestone Scale (Capute et al, 1986) and they continued to utilize the CDC's Developmental Milestones to gauge developmental level.…”
Section: Evaluation Methodsmentioning
confidence: 99%
“…For example, standard of care in diagnosing ASD involves an objective observation of behavior (Hyman et al., 2020 ) and a diagnosis of IDD requires consideration of performance on standardized intellectual testing (American Psychiatric Association, 2013 ). While there is emerging research supporting concordance between in‐person and telehealth administered standardized intellectual testing (Hamner et al., 2021 ; Harder et al., 2020 ; McDermott et al., 2023 ; Ng et al., 2023 ; Wright, 2020 ), much less is known about frequency at which providers are evaluating for IDD over telehealth or their certainty in making the diagnosis within the context of this evaluation modality. Notably, there has been very little research comparing evaluation of neurodevelopmental and psychiatric disorders other than ASD before and during the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Such remote assessments have gained particular importance due to COVID-19 pandemic regulations encouraging physical distancing and are becoming perceived as a valuable resource whenever face-to-face encounters are not feasible. Accumulated empirical evidence on TeleNP has supported the feasibility, reliability, validity, and acceptability of administering neuropsychological tests remotely in a variety of contexts for both adult and pediatric populations [43][44][45][46][47][48][49][50][51]. TeleNP and in-person assessment scores have shown no significant differences [43,[46][47][48][49][51][52][53][54].…”
Section: Introductionmentioning
confidence: 99%
“…Accumulated empirical evidence on TeleNP has supported the feasibility, reliability, validity, and acceptability of administering neuropsychological tests remotely in a variety of contexts for both adult and pediatric populations [43][44][45][46][47][48][49][50][51]. TeleNP and in-person assessment scores have shown no significant differences [43,[46][47][48][49][51][52][53][54]. A systematic review conducted by Ruffini et al [43] on the comparison of TeleNP and in-person assessment (23 studies, N = 2193 children, targeting language, memory, and executive functions) reported no significant differences between the two methods of administration, taking into account the type of tasks and stimuli used [43].…”
Section: Introductionmentioning
confidence: 99%